Debunking the Myth: Do Maternal-Fetal Medicine Fellows Negatively Impact Resident Obstetrical Skills? - Sarah K. Dotters-Katz; Matthew Grace; R Phillips Heine; Katie Propst (Thieme Medical Publishers, Inc., 2020)
Objective Residency applicants often express concern that fellows negatively impact surgical opportunities, especially with less common procedures. We sought to describe the impact of maternal-fetal medicine (MFM) fellows on resident surgical opportunities. Study Design Anonymous 27-question e-survey sent to obstetrics and gynecology (OBGYN) residents in the United States and Puerto Rico in March 2018. Questions included experience as primary surgeon, for fourth year residents only, comfort performing procedures postresidency, and demographics. Residents from programs with MFM fellows (pMFM) were compared with those without (nMFM). Descriptive statistics used as appropriate. Regression was performed, controlling for significant variables. Results A total of 417 residents completed the survey; 275 (66%) from nMFM and 142 (33%) from pMFM. PMFM residents were more likely to have >7 residents/year, be from an academic residency, and less likely to be planning to practice obstetrics postresidency (all, p < 0.01). Plan to pursue MFM fellowship did not differ. NMFM residents were more likely to have been primary surgeon on a vacuum assisted delivery (77 vs. 63%, p < 0.01). No difference in primary surgeon experience was seen for forceps delivery, breech deliveries, third- or fourth-degree repairs, cerclage, or cesarean hysterectomy. With regard to comfort performing procedures postresidency, vacuum-assisted vaginal delivery (VAVD) was more likely among nMFM trainees, no other differences seen. In regression models, no differences in likelihood of comfort performing procedures postresidency for any procedures based on the presence of MFM fellows were seen. Among pMFM residents, 94% stated fellows positively impacted their learning. Conclusion MFM fellows do not appear to impact residents' perceived competency in obstetric procedures and the majority of trainees report that fellows positively impact their education.